Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To find the antiderivative [tex]\( F(x) \)[/tex] of the function [tex]\( f(x) = \frac{2}{x^2} + 8 \cdot x^6 \)[/tex], we follow these steps:
1. Break down the function into simpler parts:
[tex]\[ f(x) = \frac{2}{x^2} + 8 \cdot x^6 \][/tex]
2. Rewrite the function in terms of exponents:
[tex]\[ f(x) = 2 \cdot x^{-2} + 8 \cdot x^6 \][/tex]
3. Integrate each term separately:
- For [tex]\( 2 \cdot x^{-2} \)[/tex]:
The antiderivative of [tex]\( x^{-n} \)[/tex] where [tex]\( n \neq 1 \)[/tex] is [tex]\( \frac{x^{-n+1}}{-n+1} \)[/tex].
Here, [tex]\( n = 2 \)[/tex], so:
[tex]\[ \int 2 \cdot x^{-2} \, dx = 2 \cdot \frac{x^{-2+1}}{-2+1} = 2 \cdot \frac{x^{-1}}{-1} = -2 \cdot x^{-1} = -\frac{2}{x} \][/tex]
- For [tex]\( 8 \cdot x^6 \)[/tex]:
The antiderivative of [tex]\( x^n \)[/tex] is [tex]\( \frac{x^{n+1}}{n+1} \)[/tex].
Here, [tex]\( n = 6 \)[/tex], so:
[tex]\[ \int 8 \cdot x^6 \, dx = 8 \cdot \frac{x^{6+1}}{6+1} = 8 \cdot \frac{x^7}{7} = \frac{8x^7}{7} \][/tex]
4. Combine the results:
[tex]\[ F(x) = \left( -\frac{2}{x} \right) + \left( \frac{8x^7}{7} \right) \][/tex]
5. Add the constant of integration [tex]\( C \)[/tex]:
[tex]\[ F(x) = \frac{8 \cdot x^7}{7} - \frac{2}{x} + C \][/tex]
So, the antiderivative of [tex]\( f(x)=\frac{2}{x^2}+8 \cdot x^6 \)[/tex] is:
[tex]\[ F(x) = \boxed{\frac{8 \cdot x^7}{7} - \frac{2}{x}} + C \][/tex]
1. Break down the function into simpler parts:
[tex]\[ f(x) = \frac{2}{x^2} + 8 \cdot x^6 \][/tex]
2. Rewrite the function in terms of exponents:
[tex]\[ f(x) = 2 \cdot x^{-2} + 8 \cdot x^6 \][/tex]
3. Integrate each term separately:
- For [tex]\( 2 \cdot x^{-2} \)[/tex]:
The antiderivative of [tex]\( x^{-n} \)[/tex] where [tex]\( n \neq 1 \)[/tex] is [tex]\( \frac{x^{-n+1}}{-n+1} \)[/tex].
Here, [tex]\( n = 2 \)[/tex], so:
[tex]\[ \int 2 \cdot x^{-2} \, dx = 2 \cdot \frac{x^{-2+1}}{-2+1} = 2 \cdot \frac{x^{-1}}{-1} = -2 \cdot x^{-1} = -\frac{2}{x} \][/tex]
- For [tex]\( 8 \cdot x^6 \)[/tex]:
The antiderivative of [tex]\( x^n \)[/tex] is [tex]\( \frac{x^{n+1}}{n+1} \)[/tex].
Here, [tex]\( n = 6 \)[/tex], so:
[tex]\[ \int 8 \cdot x^6 \, dx = 8 \cdot \frac{x^{6+1}}{6+1} = 8 \cdot \frac{x^7}{7} = \frac{8x^7}{7} \][/tex]
4. Combine the results:
[tex]\[ F(x) = \left( -\frac{2}{x} \right) + \left( \frac{8x^7}{7} \right) \][/tex]
5. Add the constant of integration [tex]\( C \)[/tex]:
[tex]\[ F(x) = \frac{8 \cdot x^7}{7} - \frac{2}{x} + C \][/tex]
So, the antiderivative of [tex]\( f(x)=\frac{2}{x^2}+8 \cdot x^6 \)[/tex] is:
[tex]\[ F(x) = \boxed{\frac{8 \cdot x^7}{7} - \frac{2}{x}} + C \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.